2022
DOI: 10.3390/ijms23084142
|View full text |Cite
|
Sign up to set email alerts
|

Genome Integrity and Neurological Disease

Abstract: Neurological complications directly impact the lives of hundreds of millions of people worldwide. While the precise molecular mechanisms that underlie neuronal cell loss remain under debate, evidence indicates that the accumulation of genomic DNA damage and consequent cellular responses can promote apoptosis and neurodegenerative disease. This idea is supported by the fact that individuals who harbor pathogenic mutations in DNA damage response genes experience profound neuropathological manifestations. The rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…SIRTs and nervous system diseases. Nervous system diseases directly affect the lives of hundreds of millions of people worldwide, 733 and one in every nine people dies due to a disorder of the nervous system. 734 Recently, there has been a gradual increase in research on the role of SIRTs in neurological diseases.…”
Section: ) Other Intestinal Diseasesmentioning
confidence: 99%
“…SIRTs and nervous system diseases. Nervous system diseases directly affect the lives of hundreds of millions of people worldwide, 733 and one in every nine people dies due to a disorder of the nervous system. 734 Recently, there has been a gradual increase in research on the role of SIRTs in neurological diseases.…”
Section: ) Other Intestinal Diseasesmentioning
confidence: 99%
“…More complex lesions that block the progress of RNA or DNA polymerases can result in arrested transcription or replication, respectively, leading to senescence or cell death—fates that culminate in degenerative diseases typically associated with aging [ 11 ]. The CNS is especially prone to degeneration following persistent DNA damage accumulation, primarily as a result of the post-mitotic character of neuronal cells but also due to the limited DNA repair repertoire associated with non-proliferating cells [ 12 ]. The review here will present data that support the role of oxidative DNA damage in the pathogenic process of an SCI, though findings are often contradictory, with broad gaps in our current knowledge.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…If these lesions remain unresolved, several detrimental outcomes could occur, such as mutagenesis, DNA replication fork collapse, or RNA transcription blockage, leading to cellular outcomes such as transformation, apoptosis, or senescence. Fortunately, organisms have developed several repair mechanisms to resolve DNA damage and restore DNA to its natural state [ 11 , 12 ]. Depending on the type of DNA lesion, a different mechanism is called upon.…”
Section: The Dna Damage Response Is Understudied In Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is a shared hallmark of aging and neuro­degeneration caused by persistent oxidative stress and increased mitochondrial Ca 2+ uptake, leading to the impairment of the electron transport chain and a decrease in ATP production. , Considerable efforts have been made to identify the key molecular determinants for these pathogenic events, and several candidates have been identified. We have previously shown that mitochondria-targeting electron and radical scavengers, e.g., nitroxides XJB-5-131 and JP4-039, are effective in vivo to mediate injury-induced neuronal death and delay the onset of neuro­degenerative diseases such as HD, TBI, and progeria. These results inspired us to investigate the effect of mitochondria-targeting PARP-1 inhibitors . The poly­(ADP-ribose) polymerase (PARP) family of enzymes plays an important role in DNA repair, genome maintenance, chromatin remodeling, transcription regulation, stress response, and regulation of cell death. , PARPs catalyze the PARylation of target proteins by tagging them with polymers of ADP-ribose (PAR), using NAD + as substrate, and releasing nicotinamide as a side-product.…”
mentioning
confidence: 99%